2006
DOI: 10.1161/circulationaha.104.529511
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Acute and Chronic Myocardial Infarcts by Multidetector Computed Tomography

Abstract: Background-We evaluated whether contrast-enhanced multidetector computed tomography (CE-MDCT) might characterize myocardial infarct (MI) with patterns similar to those obtained by contrast-enhanced magnetic resonance (CE-MR) and studied the underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
250
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(268 citation statements)
references
References 30 publications
12
250
1
5
Order By: Relevance
“…Экспериментальные исследования на жи-вотных с индуцированной острой окклюзией коронарной артерии и последующей реперфу-зией продемонстрировали, что зона ОГК мио-карда на КТ-изображениях сердца соответству-ет зоне ИМ по данным гистологического анали-за [11,12]. Максимальная рентгеновская плот-ность в зоне ОГК достигается на 5-7 минуте от момента введения контрастного препарата с последующим постепенным снижением контра-стирования [12].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Экспериментальные исследования на жи-вотных с индуцированной острой окклюзией коронарной артерии и последующей реперфу-зией продемонстрировали, что зона ОГК мио-карда на КТ-изображениях сердца соответству-ет зоне ИМ по данным гистологического анали-за [11,12]. Максимальная рентгеновская плот-ность в зоне ОГК достигается на 5-7 минуте от момента введения контрастного препарата с последующим постепенным снижением контра-стирования [12].…”
Section: Discussionunclassified
“…Максимальная рентгеновская плот-ность в зоне ОГК достигается на 5-7 минуте от момента введения контрастного препарата с последующим постепенным снижением контра-стирования [12]. Основываясь на собственном многолетнем опыте проведения отсроченной КТ больным ОИМ, мы также считаем, что опти-мальное соотношение контрастность/шум на КТ-изображениях в зоне инфаркта регистриру-ется на 7 минуте от начала внутривенного вве-дения контрастного препарата [14].…”
Section: Discussionunclassified
“…Multidetector CT has been found to have contrast patterns similar to first-pass perfusion and delayed enhancement MRI, and scar size as quantified by delayed imaging CT has been shown to correlate well with MRI. [11,12] For both multidetector CT and MRI, delayed hyperenhancement is thought to result from the slow washout of contrast from the region of infarcted myocardium. To perform a delayed enhancement scan, scanning is performed between 5 and 10 minutes after contrast material injection.…”
Section: Ischemic Cardiomyopathy/obstructivementioning
confidence: 99%
“…58 Myocardial DE on MDCT allows the early evaluation of myocardial viability immediately after PCI without additional injection of contrast agent. 59 We previously showed that contrast DE patterns might be reliably useful in predicting functional recovery of the post-ischemic myocardium and LV remodeling, 60 and the size of the myobecause computation of FFRCT requires a supercomputer.…”
Section: Fractional Flow Reserve (Ffr) Ct Mpi and Delayed Enhancemenmentioning
confidence: 99%